2021
DOI: 10.3390/ijms22020948
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Responses and Thermotolerance in Maize

Abstract: High temperatures causing heat stress disturb cellular homeostasis and impede growth and development in plants. Extensive agricultural losses are attributed to heat stress, often in combination with other stresses. Plants have evolved a variety of responses to heat stress to minimize damage and to protect themselves from further stress. A narrow temperature window separates growth from heat stress, and the range of temperatures conferring optimal growth often overlap with those producing heat stress. Heat stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 118 publications
(176 reference statements)
3
70
0
1
Order By: Relevance
“…Davletova et al (2005) also showed, using knockout (KO) mutants of cytosolic ascorbate peroxidase, an ROS scavenging enzyme and that heat shock transcription factor 21 (HSF21/AtHSFA4) is involved in H 2 O 2 stress sensing, suggesting a close link between the HSF and ROS [65]. A few other major ROS responsive TFs include MYB domain protein 44 (MYB44), Heat Stress transcription factor A-4A (HSFA4A), and Ethylene Responsive Element-Binding Factor 6 (ERF6) [53,[67][68][69][70][71]. Similarly, heat stress induction has been shown to trigger the expression of heat shock proteins HSP17.6 and HSP18.2 in Arabidopsis cell cultures.…”
Section: Role Of Ros During High Temperatures Stressmentioning
confidence: 99%
“…Davletova et al (2005) also showed, using knockout (KO) mutants of cytosolic ascorbate peroxidase, an ROS scavenging enzyme and that heat shock transcription factor 21 (HSF21/AtHSFA4) is involved in H 2 O 2 stress sensing, suggesting a close link between the HSF and ROS [65]. A few other major ROS responsive TFs include MYB domain protein 44 (MYB44), Heat Stress transcription factor A-4A (HSFA4A), and Ethylene Responsive Element-Binding Factor 6 (ERF6) [53,[67][68][69][70][71]. Similarly, heat stress induction has been shown to trigger the expression of heat shock proteins HSP17.6 and HSP18.2 in Arabidopsis cell cultures.…”
Section: Role Of Ros During High Temperatures Stressmentioning
confidence: 99%
“…Maize tassels (male flowers) growing at the top of the plant were found to be vulnerable to low-level heat stress and this affected pollen viability (Dong et al, 2021;Wang et al, 2021). At the flowering stage, high temperatures inhibited anther dehiscence, pollen viability, and pollen germination, which caused kernel abortion and maize yield reduction (Carberry et al, 1989;Bakhtavar et al, 2015;Hatfield and Prueger, 2015;Li and Howell, 2021;Wang et al, 2021). Additionally, high temperatures caused a delay in the anthesis-silking interval (ASI) of maize, resulting in reduced kernel number, although plenty of pollen was still present (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DNAJC17 depletion induced widespread changes in AS of endogenous genes in HeLa cells. These findings uncovered a novel role for DNAJC17 in splicing-related processes and suggest that splicing impairment may contribute to its essential function in early development [166].…”
Section: Rna Processing Regulation In Response To Heat Shockmentioning
confidence: 90%
“…More recently, a role in splicing regulation was also described for DNAJC17, a member of the HSP40 family [166]. DNAJC17 is an essential protein that was identified as a susceptibility factor for congenital hypothyroidism and myeloproliferative disorders.…”
Section: Rna Processing Regulation In Response To Heat Shockmentioning
confidence: 99%